PENGARUH ALOKASI DANA PERIMBANGAN TERHADAP KETIMPANGAN EKONOMI REGIONAL DI PROVINSI KALIMANTAN BARAT - B01108116, Tri Bunga Kecilung (Jurnal Pembangunan dan Pemerataan, 2013)
Thesis titled "The Effect of Balance Fund Allocations Against Regional Economic Disparities in West Borneo Province". The purpose of this study was to analyze the effect of the Special Allocation Fund, the General Allocation Fund and Revenue Sharing on regional economic disparities districts / cities in West Borneo. This study uses quantitative methods, namely the processing of secondary data which is then carried out an analysis of the research object in accordance with the objectives of the study. The data used are secondary data from the period 2006-2010 are sourced from the Bureau of Local Government Finance of West Borneo and Central Bureau of Statistics. From the research results can be seen that the Special Allocation Fund and the General Allocation Fund exacerbate regional economic disparities districts / cities in West Borneo, while the Revenue Sharing can reduce the level of regional economic disparities districts / cities in West Borneo. Keywords: Balance Fund, Special Allocation Fund, the General Allocation Fund, Revenue Sharing, Williamson Index